EFFECTS OF MANAGERIAL OWNERSHIP AND PROFITABILITY ON COMPANY VALUE MEDIATED BY DEBT POLICY AS INTERVENING VARIABLE - Giantoro Pamungkas (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2020)
This study aims to determine whether there are effects between managerial ownership and profitability on company value, by using debt policy as intervening variable. The type of research used was descriptive and associative research. The research population was manufacturing companies listed in IDX period of 2011-2015 as many as 80 companies. By using purposive sampling method, 25 companies as sample were obtained. The data used was secondary data. Data analysis used classical assumption test, path analysis and partial test (t-test), using SPSS (Statistics Product and Service Solution) 17 for windows. The results indicate that there are no effects of managerial ownership on company value, there are positive and significant effects of profitability on company value, there are no effects of debt policy on company value, there are positive and significant effects of managerial ownership on debt policy, there are negative but not significant effects of profitability on debt policy, there are no effect of managerial ownership on company value with Debt Policy mediated, there are negative effects of profitability on company value with Debt Policy mediated